Unexpected thoracic injury caused by a falling bullet in a metropolis - Mustafa Akman (Wolters Kluwer Medknow Publications, 2023)
The incident of being wounded by free-falling bullets is not usual in provinces where there is limited civilian armament in large metropolises. Cases that are wounded by falling bullet wounding apply to health-care institutions with major clinical manifestations. The patient was admitted with minor complaints, which manifested itself with mild back pain and spotting bleeding. An ovoid-style open wound was detected on the left scapula. Radiographic examination showed a semi-ovoid bullet-like radiodensity image inside the thoracic wall. In the evaluation performed under general anaesthesia, a bullet was found in the thoracic wall and was removed. In the standard follow-ups after the procedure, full recovery was achieved in the early period. Bullet wounds might be experienced outside of the battlefields without any direct fire, and these cases might not manifest the signs of gunshot injury. The cruciality of radiography in tackling diagnostic challenges was put forward.